Educational attainment for youth who were maltreated in adolescence: Investigating the influence of maltreatment type and foster care placement. (May 2018) - Cage, Jamie
Abstract: Decades of research have consistently shown a link between foster care and low rates of high school completion. Despite the overwhelming knowledge surrounding this association, it remains unclear whether the low rates of high school completion are due to placement in foster care or the maltreatment and other contextual factors that foster care youth have experienced. This study examined the extent to which (a) maltreatment type and (b) foster care placement were associated with the educational attainment of 337 maltreated adolescents. Logistic regression analyses were conducted using two waves of data and the ACR dataset of the National Survey of Child and Adolescent Well-Being (NSCAW). After controlling for academic risk factors related to the adolescents (age, race, and gender), their family (household poverty and parental education), and their environment (community environment), neither maltreatment type nor foster care placement status were associated with subsequent high school completion. Overall, only 58% of the maltreated adolescents reported completing their education. That is about 15% less than the national average at the time data were collected for this study. Results, overall, suggest a need for educational supports and interventions for youth who experience maltreatment during their adolescent years, regardless of maltreatment type and foster care placement.